All-optical encrypted movie - Mosso Solano, Edward Fabián (2011)
We introduce for the first time the concept of an all-optical encrypted movie. This movie joints several encrypted frames corresponding to a time evolving situation employing the same encoding mask. Thanks to a multiplexing operation we compact the encrypted movie information into a single package. But the decryption of this single package implies the existence of cross-talk if we do not adequately pre-process the encoded information before multiplexing. In this regard, we introduce a grating modulation to each encoded image, and then we proceed to multiplexing. After appropriate filtering and synchronizing procedures applied to the multiplexing, we are able to decrypt and to reproduce the movie. This movie is only properly decoded when in possession of the right decoding key. The concept development is carried-out in virtual optical systems, both for the encrypting and the filtering-decrypting stages. Experimental results are shown to confirm our approach.